Pemanfaatan Limbah Ampas Kelapa (Cocos nucifera Lin) Sebagai Tepung Dalam Pembuatan Mi Basah - Elsa Desy Pratiwi; Lilik Hendrarini; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2016)
In Indonesia, almost 75 % of waste is dominated by organic type that if is not handled properly will cause unpleasant odor and become the breeding sites for bacteria that can potentially inter-fere public health. Jenang Mirah Industry in Josari Village, Jetis, Ponorogo, East Java produces ± 1.2 quintal of organic waste in form of coconut (Cocos nucifera Lin ) pulp that has not been yet treated adequately. The crude fiber content in coconut pulp can be utilized as flour to sub-stitute wheat flour in food making, such as wet noodles. The purpose of this study was to deter-mine the differences of organoleptic test and shelf life among wet noodles produced from four different formulations of coconut pulp flour and wheat flour, by conducting a post-test only with control group designed quasi-experiment. The formulations used were: Formulation I, 300 gr coconut pulp flour and 200 gr wheat flour; Formulation II, 250 gr coconut pulp flour and 250 gr wheat flour; Formulation III, 200 gr coconut pulp flour and 300 gr wheat flour; and Formulation IV or the control, 500 gr wheat flour only. The experiment was using five panelists and the data were statistically analyzed by Kruskall-Wallis test at 5 % level of significance.The results show-ed that Formulation III is the most accepted by consumers (the average score was 3.98 with ra-ting category